Growth-Promoting Effects of Grass Root-Derived Fungi Cadophora fastigiata, Paraphoma fimeti and Plectosphaerella cucumerina on Spring Barley (Hordeum vulgare) and Italian Ryegrass (Lolium multiflorum) - Izolda Pašakinskienė; Violeta Stakelienė; Saulė Matijošiūtė; Justas Martūnas; Marius Rimkevičius; Jurga Būdienė; Algis Aučina; Audrius Skridaila (Microorganisms)
Many endophytic fungi are approved as plant growth stimulants, and several commercial biostimulants have already been introduced in agricultural practice. However, there are still many species of fungi whose plant growth-promoting properties have been understudied or not studied at all. We examined the growth-promoting effect in spring barley (Hordeum vulgare) and Italian ryegrass (Lolium multiflorum) induced by three endophytic fungi previously obtained from the roots of Festuca/Lolium grasses. Surface-sterilized seeds were inoculated with a spore suspension of Cadophora fastigiata (isolate BSG003), Paraphoma fimeti (BSG010), Plectosphaerella cucumerina (BSG006), and their spore mixture. Before harvesting, the inoculated plants were grown in a greenhouse, with the barley being in multi-cavity trays for 30 days and ryegrass being placed in an original cylindric element system for 63 days. All three newly tested fungi had a positive effect on the growth of the barley and ryegrass plants, with the most pronounced impact observed in their root size. The fungal inoculations increased the dry shoot biomass between 11% and 26% in Italian ryegrass, but no such impact was observed in barley. The highest root increment was observed in barley. Herein, P. cucumerina and C. fastigiata inoculations were superior to other treatments, showing an increase in root dry weight of 50% compared to 20%, respectively. All fungal inoculations significantly promoted root growth in Italian ryegrass, resulting in a 20–30% increase in dry weight compared to non-inoculated plants. Moreover, a strong stimulatory effect of the fungi-emitted VOCs on the root development was observed in plate-in-plate arrays. In the presence of C. fastigiata and P. cucumerina cultures, the number of roots and root hairs in barley seedlings doubled compared to control plants. Thus, in our study, we demonstrated the potential of the grass root-derived endophytes C. fastigiata, P. fimeti, and P. cucumerina as growth promoters for spring barley and Italian ryegrass. These studies can be extended to other major crops and grasses by evaluating different fungal isolates.